METANIL YELLOW - AN AZO DYE INDUCED HISTOPATHOLOGICAL AND ULTRASTRUCTURAL CHANGES IN ALBINO RAT (RATTUS NORVEGICUS) - RITUPARNA SARKAR,; APURBA RATAN GHOSH, (The Bioscan, 2012)
The azo dye Metanil Yellow is used in different food items for dyeing and colouring purposes. The chronic exposure of this non-permitted food colour as well as additive in albino rat (Rattus norvegicus) for 30 days at a dose of 3.0g/kg body weight was invested through histopathological and ultrastructural changes in stomach, intestine, liver and kidney. Several changes were found under histopathological as well as ultrastructural observations. Histopathological lesions as observed in stomach were disruption of gastric folds, profuse secre- tion of mucus, necrosis in columnar epithelial cells and gastric glands. In intestine, the villi were damaged severely. The absorptive columnar epithelial cells were totally damaged in some regions, brush border and lamina propria were disrupted due to toxicity. Histopathological lesions were also observed in the liver and kidney of albino rats. In liver, there was an extensive degeneration of hepatocytes, diminish in cytoplasmic content. Appearance of pycnosis of nuclei and damage occurred in the central vein regions. In kidney, necrosis of tubular epithelium, cloudy swelling of epithelial cells of renal tubules and disruption in Bowman’s capsule were also prominent features of toxicosis. Under ultramicroscopic observations lesions were found in the mucosal folds and columnar epithelial cells of stomach and intestine. Several changes were also shown in the absorptive columnar epithelial cells as well as in the microvilli of intestine. All these alterations marked the toxic effects of Metanil Yellow in rat.